Auditory evoked BOLD responses in awake compared to lightly anaesthetized zebra finches - Van Ruijssevelt, L. (Sci Rep, 2017)
Functional magnetic resonance imaging (fMRI) is increasingly used in cognitive neuroscience and has become a valuable tool in the study of auditory processing in zebra finches, a well-established model of learned vocal communication. Due to its sensitivity to head motion, most fMRI studies in animals are performed in anaesthetized conditions, which might significantly impact neural activity evoked by stimuli and cognitive tasks. In this study, we (1) demonstrate the feasibility of fMRI in awake zebra finches and (2) explore how light anaesthesia regimes affect auditory-evoked BOLD responses to biologically relevant songs. After an acclimation procedure, we show that fMRI can be successfully performed during wakefulness, enabling the detection of reproducible BOLD responses to sound. Additionally, two light anaesthesia protocols were tested (isoflurane and a combination of medetomidine and isoflurane), of which isoflurane alone appeared to be the most promising given the high success rate, non-invasive induction, and quick recovery. By comparing auditory evoked BOLD responses in awake versus lightly anaesthetized conditions, we observed overall effects of anaesthetics on cerebrovascular reactivity as reflected in the extent of positive and negative BOLD responses. Further, our results indicate that light anaesthesia has limited effects on selective BOLD responses to natural versus synthetic sounds.